Pengaruh Promosi terhadap Loyalitas Konsumen Produk UMKM Tersertifikasi Halal (Studi Kasus Mahasiswa UIN Kiai Haji Achmad Siddiq Jember) - Nasirudin Al Ahsani; Nita Andriani (Fakultas Dakwah IAIN Jember, 2021)
In Islamic business, business people do not only think about how all their business activities get abundant profits but also how to reap God's blessings from the business. This is what makes business people continue to strive to make their business in accordance with the Sharia. For instance, CV Bun Prink which sells its small micro medium enterprises (UMKM) products, namely Luwak (palm civet) coffee. CV. Bun Prink is a provider of wild Luwak Coffee in the form of powder, roasted seeds, (cleaned) dry beans and dirty beans obtained from rural areas in Jember, East Java, Indonesia. Meanwhile the general requirements for halal certification are: First, the products must be of quality and hygienic products as the halal guarantee standard is a form of claim that the products fall into certain categorizations. Second, to provide protection for local industry from imported goods. After obtaining a halal certification, the community will feel safer and more comfortable in buying luwak coffee products, especially when there is a statement that luwak coffee is the most expensive coffee in the world, increasing the consumers' trust from the promotion. Therefore, the current study will discuss about the effect of promotion on consumer's loyalty for halal-certified UMKM products by quantitative research methods. The research finding, generated from the questionnaire result of students of UIN Achmad Siddiq who are all Muslims as the respondents, shows that the promotion for halal-certified UMKM products have a significant and positive influence on consumer's loyalty. These results indicate that the existence of promotions on UMKM Products Kopi Luwak CV Bun Prink has a great opportunity in influencing the customer's loyalty.